Eco-friendly bio-composite sheets: a study on the utilization of banana peels, cassava starch, and banana stem fibers - Ishara, G.K.K; Koliyabandara, Pabasari A; Samarakoon, Gamunu (Frontiers in Sustainability, 2024)
Massively using conventional plastics has led to significant environmental issues, including harm to ecosystems, wildlife, and human health, contributions to greenhouse gas emissions, and resource depletion through their extraction and production. Thus, there is an urgent imperative to seek sustainable alternatives like bio-composites. This research established the viability of banana peels and cassava starch for eco-friendly bio-composite sheets, offering insights into their properties and performance The bio-composite materials, composed of banana peels, cassava starch, banana stem fiber, glycerol, and acetic acid, were prepared in different weight-based proportions. The preparation process involved cleaning, drying, blending, and molding the materials to produce consistent bio-composite samples. The properties and performance of the composite samples were assessed for water absorption, moisture content, and tensile strength. Notably, the combination of banana peels and cassava in a 1:2 ratio, along with banana stem fiber, demonstrated favorable attributes, including reduced water absorption (ranging from 6.42 to 30.91%), desirable moisture content (ranging from 8.06 to 11.27%), and increased tensile strength (ranging from 5.345 to 11.892 MPa). These findings confirm the viability of using banana peels and cassava starch in producing bio-composite sheets, offering a sustainable alternative to conventional plastics. This study contributes to the field of sustainable materials by providing insights into the properties and performance of bio-composites, thereby supporting the development of eco-friendly bio-composite sheets.